1996
DOI: 10.1002/hep.510230529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liver transplantation on QT interval prolongation and autonomic dysfunction in end-stage liver disease

Abstract: Both a prolonged QT interval and disturbance of autonomic nervous system function are markers of poor prognosis in patients with diabetes mellitus and alcoholic liver disease (ALD). We studied the prevalence of abnormal QT interval and autonomic nervous system dysfunction in 53 consecutive patients with end-stage liver disease before and after orthotopic liver transplantation (OLT). The maximum QT interval in any lead (QTmax) was assessed by two independent observers. The QTmax, corrected for heart rate (QTcma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
84
2
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(102 citation statements)
references
References 19 publications
12
84
2
4
Order By: Relevance
“…In addition, partial or full reversal of QT prolongation following liver transplantation has also been noted[14,26-31]. Contrary to these findings, in our study, QT c prolongation was not significantly influenced by etiology, age, beta-blocker use, or transplantation.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…In addition, partial or full reversal of QT prolongation following liver transplantation has also been noted[14,26-31]. Contrary to these findings, in our study, QT c prolongation was not significantly influenced by etiology, age, beta-blocker use, or transplantation.…”
Section: Discussioncontrasting
confidence: 96%
“…A number of studies have evaluated the association between QT prolongation and severity of ESLD as measured by Child-Pugh scores[14,19,24,25,28,36]. The majority of such studies have shown an increase in QT prolongation in association with higher Child-Pugh scores with the exception of studies done by Carey et al[27] and Adigun et al[30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies revealed impaired hemodynamic responses to physical (exercise) and pharmacological stress [2, 3]. These abnormalities were initially believed to be a direct toxic effect of alcohol; however, subsequent studies in human and animal models of nonalcoholic cirrhosis demonstrated similar manifestation of blunted cardiac contractility in response to stress and electrophysiological abnormality [46]. This disorder was formally termed as “cirrhotic cardiomyopathy.” In this review, we summarized the pathyphysiology and clinical significance of cirrhotic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The major electrocardiographic change in cirrhosis is the prolongation of the QT interval, which is related to the severity of cirrhosis, and is independent of its etiology [3,4,5]. The prolongation of QT interval is associated with malignant ventricular arrhythmia and sudden cardiac death in end-stage liver disease (ESLD) and myocardial infarction [5,6,7].…”
Section: Introductionmentioning
confidence: 99%